2022
DOI: 10.21203/rs.3.rs-2196912/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Androgen dihydrotestosterone promotes bladder cancer cell proliferation and invasion via EPPK1-mediated MAPK/JUP signaling

Abstract: The incidence of bladder cancer (BLCA) in men is higher than that of women. Differences in androgen levels between men and women are considered the main causes of incidence rate differences. In this study, dihydrotestosterone (DHT) could significantly increase cell proliferation and invasion of BLCA cell line. In addition, BLCA formation and metastatic rates were higher in N-butyl-N-(4-hydroxybutyl) nitrosamine (BBN) treated male mice than in female and castrated male mice in vivo. However, immunohistochemistr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…EPPK1 is a member of the plakin set, of which, most members were abundant in diverse tissues and organs 30 . EPPK1 was reported to be expressed in diverse developmental, progenitor, and regenerative cells, expressly in cervical and bladder cancer cells, 18,20 suggesting that EPPK1 might be a potent regulatory factor in malignancy progression. Furthermore, the abnormally expressed EPPK1 was also verified in esophageal squamous cell carcinoma 22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EPPK1 is a member of the plakin set, of which, most members were abundant in diverse tissues and organs 30 . EPPK1 was reported to be expressed in diverse developmental, progenitor, and regenerative cells, expressly in cervical and bladder cancer cells, 18,20 suggesting that EPPK1 might be a potent regulatory factor in malignancy progression. Furthermore, the abnormally expressed EPPK1 was also verified in esophageal squamous cell carcinoma 22 .…”
Section: Discussionmentioning
confidence: 99%
“…EPPK1, a usual cell linker protein, is located on the cytoplasmic membranes junction and able to integrate cytoskeleton to myofilaments. More importantly, EPPK1 has the ability to regulate the proliferation of tumor cells 18 . Emerging evidence indicated that EPPK1 was dysregulated in various malignancies, such as bladder urothelial carcinoma, cervical cancer, hepatocellular carcinoma, and esophageal squamous cell carcinoma 19‐22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The testis can convert androgens into dihydrotestosterone, a pure androgenic steroid found exclusively in men. This conversion is carried out through the action of 5α-reductase [13]. Androgens bind to the AR in target cells to produce physiological effects [14].…”
Section: Introductionmentioning
confidence: 99%
“…It plays a role in target cell differentiation and proliferation [14,15]. Several studies have con rmed a strong link between androgens, AR, and the development and occurrence of BLCA [12][13][14][15][16]. Studies have shown that androgen and AR signals can promote the proliferation of BLCA cells.…”
Section: Introductionmentioning
confidence: 99%